Prevalence and Duration of Acute Loss of Smell or Taste in COVID-19 Patients - Lee, Yonghyun; Min, Pokkee; Lee, Seonggu; Kim, Shin-Woo (Journal of Korean medical science, 2020)
Initially, acute loss of smell (anosmia) and taste (ageusia) was not considered important symptoms for coronavirus disease 2019 (COVID-19). To determine the prevalence of these symptoms and to evaluate their diagnostic significance, we (approximately 150 physicians of the Daegu Medical Association) prospectively collected data of cases of anosmia and ageusia from March 8, 2020, via telephone interview among 3,191 patients in Daegu, Korea. Acute anosmia or ageusia was observed in 15.3% (488/3,191) patients in the early stage of COVID-19 and in 15.7% (367/2,342) patients with asymptomatic-to-mild disease severity. Their prevalence was significantly more common among females and younger individuals ( = 0.01 and < 0.001, respectively). Most patients with anosmia or ageusia recovered within 3 weeks. The median time to recovery was 7 days for both symptoms. Anosmia and ageusia seem to be part of important symptoms and clues for the diagnosis of COVID-19, particularly in the early stage of the disease.